Thermal Boundary Conductance: Visualizing Energy Transfer at Buried Interfaces in Layered Materials Using Picosecond X‐Rays (Adv. Funct. Mater. 34/2020). (19th August 2020) - Nyby, Clara; Sood, Aditya; Zalden, Peter; Gabourie, Alexander J.; Muscher, Philipp; Rhodes, Daniel; Mannebach, Ehren; Corbett, Jeff; Mehta, Apurva; Pop, Eric; Heinz, Tony F.; Lindenberg, Aaron M.
Abstract : In article number 2002282, Aaron M. Lindenberg and co‐workers demonstrate a new technique for observing interfacial heat transport in nanoscale van der Waals layered materials using time‐resolved X‐ray measurements of photoinduced thermal strain. This approach paves the way for non‐invasive, localized characterization of thermal bottlenecks in emerging 3D heterogeneous electronics where heat dissipation can severely limit performance.